Entrepreneurship - Development Tendencies and Empirical Approach 2018
DOI: 10.5772/intechopen.70834
|View full text |Cite
|
Sign up to set email alerts
|

Deinstitutionalization through Business Model Evolution: Women Entrepreneurs in the Middle East and North Africa

Abstract: Additional information is available at the end of the chapter "The first day I sold my perfumes was the best day of my life. Customers loved them. No one had ever bought such a good product at such a low price. I was overjoyed with the success, even though I worried about getting caught running my own business…In the early years, I couldn't even open my own Abstract This chapter is among the first to examine the interplay between deinstitutionalization and the rollout of novel business models by women entrepre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…The final context involves Fatima Azoulay, a middle-aged serial entrepreneur from Morocco. Her story came to light as one of 95 detailed case studies of women entrepreneurs in seven Middle East and North African (MENA) countries (Hunt & Ortiz-Hunt, 2017).…”
Section: The Kinetic Female Serial Entrepreneur From Marrakechmentioning
confidence: 99%
“…The final context involves Fatima Azoulay, a middle-aged serial entrepreneur from Morocco. Her story came to light as one of 95 detailed case studies of women entrepreneurs in seven Middle East and North African (MENA) countries (Hunt & Ortiz-Hunt, 2017).…”
Section: The Kinetic Female Serial Entrepreneur From Marrakechmentioning
confidence: 99%
“…Coleman's theory explicates three interrelated mechanisms, including: (1) situational mechanisms in which entrepreneurs and their ventures are embedded (e.g. nations, markets), (2) action-formation mechanisms that explain how opportunities, goals and beliefs influence an entrepreneur's behavior and (3) transformation mechanisms that account for how the behavior of entrepreneurs brings about macro-level outcomes (Hunt and Ortiz-Hunt, 2017; Kim et al. , 2016).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In turn, this influences how individuals act and those behaviors influence the organization at the aggregate level (Distel, 2019). Recently, entrepreneurship scholars suggested that Coleman's theory of multilevel dynamics (a.k.a., Coleman's Bathtub model) can be a powerful framework for understanding the processes of entrepreneurship in developing countries (Cowen et al, 2022;Hunt and Ortiz-Hunt, 2017). Coleman's theory explicates three interrelated mechanisms, including: (1) situational mechanisms in which entrepreneurs and their ventures are embedded (e.g.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, advances in research on business models (e.g. Zott, Amit, & Massa, 2010) and opportunity development (Ardichvili, Cardozo & Ray, 2003) have not made their way into the rural entrepreneurship literature despite the rich set of tools both perspectives offer for identifying, describing, and predicting entrepreneurial action and outcomes, including those occurring among marginalized populations (Hunt & Ortiz-Hunt, 2018) and in developing economies (Webb et al, 2010).…”
Section: The Risks Of Fragmentationmentioning
confidence: 99%